Implikatur dalam Wacana Kampanye Pemilihan Legislatif 2019 - Ira Yuniati; Reni Kusmiarti; Abdi Kanizar; Hasmi Suyuthi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study is to describe a precise, detailed and in-depth understanding of the implicature in the campaign discourse in the 2019 legislative elections. The research method is a descriptive method. The data collection techniques of this research are, (1) collecting political discourse of the Legislative Candidates in print media such as advertisements, billboards, leaflets, banners, posters displayed on the roadside and public places, (2) reading political discourse in the media print such as advertisements, billboards, leaflets, banners, posters as a whole to get a general picture, (3) reread political discourse in print media such as advertisements, billboards, leaflets, banners, posters as well as mark the parts contained implicature, (4) collect the marked part into the data list. Data analysis techniques are (1) the data that has been identified and then classified based on the form of the implicature, (2) describes the data that has been classified, (3) the implicature data that has been described is then analyzed, (4) based on the results of the implicature analysis then provides interpretation, (5) ) draw conclusions of research. Based on the results of research and discussion on the language implicatures in the 2019 legislative election campaign discourse, it can be concluded that the implications in the 2019 legislative election campaign discourse found 36 data that include (1) conventional implications, 19 data found and (2) conversational / nonconventional implications found, 36 implicative data including (1) conventional implications, 19 data and (2) conversational / nonconventional implications; as many as 17 data. The dominant implicature that was found was conventional data as much as 19 data. The implication used by campaigners in attracting the attention of the public to choose them by means of speech is delivered in a certain setting and purpose, the information said tends to be different from what is intended. Keywords: Implicature, Campaign Discourse, Legislative Elections